(untitled) (Eurasian Scientific Herald, 2023)
It is important to clarify its goals and objectives, teaching content, form, methods and tools in order to organize electrical engineering education for students. From this point of view, in this article, specific aspects of organizing students’ practical training in electrical engineering have been considered.